Effect of gliricídia (Gliricidia sepium) in nitrogen nutrition on coffee plants (Coffea canephora) intercroped with banana trees in organic system of production - Coelho, Renato Alves; Silva, Gabriela Tavares Arantes; Ricci, Marta dos Santos Freire; Resende, Alexander Silva de (Coffee Science - ISSN 1984-3909, 2007)
Coffee is a crop with high economical importance to Brazil. It is cultivated on about 2,4 millions hectares spread in almost all the country. Nitrogen fertilizers are routinely used by coffee growers and alternatives to reduce their applications are important. In this study, coffee plants (Coffea canephora Pierre ex Froehn) intercroped with gliricídia (Gliricidia sepium (Jacq.) Steud.) and banana (Musa paradisiaca L.) and banana alone for shade were evaluated. After pruning of gliricidia, their leaves and branches were analysed for the biomass, decomposition rate and their influence on coffee nitrogen nutrition. Gliricidia demonstrated to be an important source of nitrogen for coffee, since it maintains the leaves above the critical levels, as compared to coffee with banana alone treatment, independently of the pruning process. Gliricidia branches were not an important source of Nitrogen due to their low content in nutrients and slow decomposition rate, reaching only 30% of the total in a period of 6 months, while the half life for leaves was 19 days.